(untitled) (Innovative professional education, 2023)
Independent work of future skilled workers is an integral part of blended learning. In the conditions of the information society, independent work is a multidimensional pedagogical phenomenon, which is not only a method or a means of learning, but is also one of the forms of educational activity of students on a level with classroom (auditory) education, and in times of limited access to face-to-face attendance at an educational institution, it becomes the main means of mastering educational theoretical material.